E-learning systems: System Quality, Information Quality and Service Quality on User Satisfaction - Heni Susilowati (Journal of Business and Management Review, 2020)
This study aims to analyze the effect of system quality, information quality and service quality on user satisfaction of e-learning systems in lectures at STEKOM University. The sampling technique used Probability Sampling with the Simple Random Sampling approach of 66 respondents then processed as research data. The method of analysis uses Multiple Linear Regression to test the hypothesis with the t test and F test. Contribution of the influence of independent variables to the dependent variable uses the Adjusted R coefficient of determination. The results show partially and simultaneously system quality, information quality and service quality have a significant effect on user satisfaction. The quality of information is the dominant variable that affects user satisfaction of the academic information system of STEKOM University lecturers. User satisfaction of 50.3% is influenced by the variables in this study, while 49.7% is influenced by other variables.